Pilot Land Reforms in Nigeria : Think Big, Start Small, Move Fast! …but Where Do We Start? - Dione-Mbaye, Nouma (World Bank, Washington, DC, 2012)
When it comes to strategy, the Chinese have a saying: 'think big, start small, but move fast.' This has been our guiding philosophy for the pilot land reforms of the World Bank-Department of International Development (DFID) sub national Investment Climate Program (ICP) in Nigeria. The challenge was to find a 'small' reform entry point from which to 'move fast' on this sensitive and difficult topic, which is more complicated than it might appear. After some research, the ICP team found that the most effective and efficient entry point was the mapping and streamlining of land procedures. Over the last four years, the team worked on implementing this approach in four Nigerian states (Cross River, Kaduna, Kano, and Lagos). This Smart Lesson shares some of our experiences in finding practical solutions for the successful implementation of streamlining activities at the sub national level.